Addressing the notion of socio-cultural continuum seen through the choral art as it developed throughout independence of ukraine: literature review - Marach, Oleksandr M.; Panasyuk, Svitlana L.; Shurdak, Mariia I.; Krivitska, Tatyana A.; Kinder, Karyna R. (My University, 2020)
Purpose of the study: The purpose of the present study is to specify the notion of socio-cultural continuum seen through the choral art as it developed throughout independence in Ukraine and to identify its main tendencies as drivers of choral art development. In this regard, the research tasks are to investigate the meaning of the concepts of “continuum”, “socio-cultural continuum,” and to identify the main socio-cultural tendencies that, in our opinion, have the most significant influence on the development of choral art. Methodology: This study used a meta-analysis approach to solve the issues raised in the research. Reference sources, peer-reviewed databases like Education Resources Information Centre (ERIC), Scopus, Arts & Humanities Database, the Choral Scholar (online journal), Google Scholar, together with open-source-published researches and books (published either in Ukrainian or English) were used to obtain the relevant information. Main findings: It was found, that the socio-cultural continuum in Ukraine of the period of independence emerges as a complex hierarchical system of phenomena characterized by an inextricable link between the Spatio-temporal parameters of human beings, society, and culture. Applications of this study: Interpreting this concept in relation to the development of choral art as an imaginary model of a single socio-cultural space-time in Ukraine (region) occurring throughout the independence period in all the continuous hierarchical multiplicity of its phenomena related to the functioning of choral art identified several major trends that, in our opinion, were influenced by the intensity and nature of such development. This period, as a transition period characterized by a change in outlook, the revival of previously forbidden traditions, and the emergence of new socio-cultural trends not only intensified the development but also caused several challenges that Ukrainian society faced. Novelty/Originality of this study: This scientific exploration was an attempt to understand the theoretical essence of this continuum and its tendencies, which in the future will allow knowing more about their positive and negative orientations and ways.
Keywords: Period of Independence; Ukraine; Choral Art; Socio-cultural Continuum